Keputusan Pembelian Berdasarkan Kualitas Produk, Harga dan Promosi - Marlius, Doni; Putri, Septina (JURNAL PUNDI, 2025)
Marketing is an important factor in company development. Marketing must always be upgraded and updated, which of course cannot be separated from the needs and desires of consumers. The purpose of this study is to analyze the effect of product quality, price and promotion on purchase decisions in the Fast Computer Store At Padang City. The method used is multiple linear regression analysis. The study population of 259 consumers and samples used by 72 respondents with slovin formula. The result shows that the variable of product quality have significant and negative impact toward purchasing decisions; the variable of prices have significant and negative impact toward purchasing decisions and the variable of promotion have significant and positive impact toward purchasing decisions.